PUBLIC HEALTH GOVERNANCE DURING THE COVID-19 PANDEMIC: A COMPARATIVE STUDY OF POLICY RESPONSES IN INDONESIA AND VIETNAM - Andrei Popescu; Maria Ionescu; Alexandru Stoica (Cognitionis Civitatis et Politicae, 2025)
The COVID-19 pandemic has posed significant challenges to public health systems worldwide, revealing the strengths and weaknesses of governance structures in responding to such crises. Indonesia and Vietnam, two countries with contrasting health infrastructures and political systems, implemented various public health policies in response to the pandemic. A comparative analysis of their approaches provides valuable insights into effective governance during global health emergencies. This study aims to compare the public health governance and policy responses of Indonesia and Vietnam during the COVID-19 pandemic. The research focuses on examining the efficiency, effectiveness, and impact of these policies in controlling the spread of the virus and safeguarding public health. A qualitative comparative approach was used, involving document analysis, policy review, and expert interviews. Data were gathered from government reports, public health documents, and media sources, supplemented by interviews with policymakers and public health experts in both countries. The study reveals that Vietnam’s early and strict lockdown measures, robust contact tracing, and centralized decision-making significantly contained the virus spread, while Indonesia’s decentralized approach faced challenges in coordination and implementation, leading to higher infection rates. Vietnam’s unified, top-down approach to public health governance was more effective in managing the pandemic compared to Indonesia’s decentralized, regionally variable response. This study emphasizes the importance of strong leadership and clear policy coordination in future health crises.